Acupuncture Can Regulate the Peripheral Immune Cell Spectrum and Inflammatory Environment of the Vascular Dementia Rat, and Improve the Cognitive Dysfunction of the Rats - Pan, Pan; Ma, Zhinan; Zhang, Zhen; Ling, Zhenzhen; Wang, Yao; Liu, Qiuping; Lin, Xiaolin; Xu, Pan; Yang, Dan; Zhi, Hui; Wang, Runmin; Zhang, Xuezhu (Frontiers in Aging Neuroscience, 2021)
Objective: To study the effects of acupuncture on peripheral immune function, inflammation, and cognitive impairment in vascular dementia (VD) rats. Methods: 2 months healthy male Wistar rats (260 - 280 g) were assigned to the following groups: normal group (Gn, n=10), sham-operated group (Gs, n=10) and operated group (n=45). The operated group was established by permanent bilateral common carotid artery occlusion (2VO). Two month after operation, the operated rats were screened by hidden platform trial and the rats with cognitive dysfunction were further randomly divided into impaired group (Gi), acupoint group (Ga) and non-acupoint group (Gna) with 10 rats in each group. The Ga group was given acupuncture treatment for 14 days with a rest every 7 days. After treatment, the Morris water maze (MWM) test was performed to evaluate the spatial learning and memory abilities of rats. The lymphocyte subsets in peripheral blood and spleen of rats were measured by flow cytometry. The levels of cytokines (IL-1β, IL-2, IL-4, IL-10, TNF-α, INF-γ), chemokines (MIP-2), and other inflammatory mediators (COX-2, iNOS) in peripheral blood and hippocampus were measured by ELISA. Results: Compared with the Gn group, the Gi rats presented long escape latencies to find the platform. After acupuncture treatment, the escape latencies of Ga group were rescued markedly when compared with the Gi group (p<0.05). The proportion of CD4+ T-lymphocytes in both spleen and peripheral blood in Ga group increased (P<0.05) in comparison with Gi group. And there is an obvious reduction of IL-1β (P<0.05), IL-2 (P<0.05), TNF-α (P<0.01), INF-γ (P<0.01), MIP-2 (P<0.05), and iNOS (P<0.01), coming along with the increased levels of IL-4 and IL-10 (p＜0.01) in the Ga group when compared with Gi group. As well, the hippocampus pro-inflammatory factors IL-1β (P<0.01), IL-2 (P<0.01), TNF-α (P<0.05), INF-γ (P<0.05), MIP-2 (P<0.05), iNOS (P<0.01) and COX-2 in the Ga group decreased, whereas the anti-inflammatory factors IL-4 and IL-10 (P<0.01) increased. Conclusion: There are abnormal immune function and peripheral inflammation in VD rats. Acupuncture can regulate the peripheral immune function and inflammation of the VD rats, and improve the cognitive dysfunction of the rats.